Pengertian, Sejarah Dan Masalah Bimbingan dan Konseling Perkembangan - Febriana, Sani Sevy; Ahfani, Destri Alviona; Aulia, Ananda Eka; Lestari, Shafika Ayudyah; Armada, Elsananda Gita; Maulana, Irham Eka (Guidance : Jurnal Bimbingan dan Konseling, 2025)
Helping students Helping students to develop in all aspects of life is the function of Developmental Guidance and Counseling. During the educational process, every aspect of individual development must be developed as much as possible. The more educators know about student development, the better they can guide them. The purpose of this study is to describe Developmental Guidance and Counseling from history to current problems. This research method uses library research which is carried out by reviewing and studying various journal literature as a reference based on the main problems being studied. The results of the study: (1) Definition of Developmental Guidance and Counseling (2) History of Developmental Guidance and Counseling (3) Principles of Developmental Guidance and Counseling (4) Components of Developmental Guidance and Counseling (5) Problems in Developmental Guidance and Counseling